JHEA, volume 19, n°2, 2021 - Full Issue - Journal System, (Journal of Higher Education in Africa, 2022)
Contents Producing Anthropological Knowledge in and of Southern Africa: A Case Study of the Anthropology Southern Africa Journal Shannon Morreira............................. 1 Beyond Academic Imperialism in Comparative Studies of the Global South: Methodological Reflections Madalitso Zililo Phiri........................ 27 African Culture and the Quest for Sustainable and Improved Indigenous Knowledge Production: Nigeria and South Africa in Perspective Harrison Adewale Idowu....................... 57 Mediation between Linguistic Hegemony and Periphery Languages in the Nobel Prize for Literature Wendo Nabea...................... 77 Recherche féministe et de genre à l’Université de Yaoundé II : examiner l’impact sur la transformation sociale Vanessa Aboudi............................. 91 Towards a New Conceptual Framework of Student Activism in South Africa Damtew Teferra & Mthokozisi Emmanuel Ntuli ...................... 107